Educard AR: Development of an AI-Powered Augmented Reality Virtual Laboratory for Anatomy and Biology Education - Laika Mae Florence M. Sigre; Noel P. Caliston; Jayvee G. Perez (CV. Media Inti Teknologi, 2026)
Background: Traditional learning in anatomy and biology often relies on static 2D materials, creating a gap in spatial comprehension and hindering student engagement.Aims: This study aimed to design, develop, and evaluate EduCard AR, a desktop virtual laboratory integrating marker-based Augmented Reality (AR) and Artificial Intelligence (AI) for immersive learning.Methods: Developed with Python and OpenCV, the system uses ArUco markers for 3D overlays (e.g., heart, DNA) and generative AI for contextual assistance. Evaluation involved technical benchmarking and usability testing with 30 students using the System Usability Scale (SUS).Results: Technical results showed a consistent 30 FPS with <50ms latency and 100% marker accuracy for key biological structures. The AI module achieved a 1.5s response time. Usability testing yielded a SUS score of 85.5 ('Excellent'), while an ISO 25010 expert evaluation resulted in a mean of 4.35 (Very Satisfactory), confirming functional suitability and usability.Conclusion: EduCard AR provides a cost-effective alternative to expensive laboratory equipment, demonstrating that AI-powered AR can effectively democratize interactive educational technologies.